Preliminary assessment of spent glauconite bed usage possibilities as a material to lightweight aggregate production. - Franus, Małgorzata; Latosińska, Jolanta (Budownictwo i Architektura / Civil and Architectural Engineering, 2009)
The presented work has shown an application of spent glauconite bed after purifi cation of wastewater for production of lightweight expanded clay aggregates. Sewage, from which it was removed Zn ions, came from technological line (zinc-works) of Communication Equipment Factory „PZL” Świdnik. Spent glauconite bed was used as an additive in lightweight aggregate production which was obtained using plastic method by sintering, at temperature 1140ºC and 1200 ºC, of spent glauconite amouts 10, 15, 20 and 25% wt. with clays from open-cast mine „Budy Mszczonowskie”. The presence of the mineral improves sinter texture, increases porosity and contributes to formation of glassy layer on the surface of the aggregates. Tests of zinc elution from lightweight aggregate samples has shown very low mobility of zinc ions. Content of zinc in water extracts obtained from lightweight aggregate is defi nitely lower than zinc concentration permitted for sewage discharge to water or soil, means that spent material is not offensive for the environment as it can be used as a high quality building product.